Poorer outcome of childhood acute lymphoblastic leukemia in the Bedouin population: A report from the Berlin‐Frankfurt‐Muenster–based Israeli national protocols. Issue 1 (8th October 2019) - Elhasid, Ronit; Nirel, Ronit; Avigad, Smadar; Avrahami, Gali; Abramov, Aya; Attias, Dina; Arad, Nira; Ballin, Ami; Ben‐Arush, Myriam; Bielorai, Bella; Burstein, Yoav; Elitzur, Sarah; et al.
Abstract: Background: Therapy outcomes for childhood acute lymphoblastic leukemia (ALL) had substantially improved in the last decades, but variability across racial and ethnic groups was identified in some clinical studies. In this study, we aimed to investigate whether such a difference in outcome is found in the diverse ethnicities in Israel as well. Methods: A retrospective study was conducted among 1154 patients (855 Jews, 195 Muslims, 52 Bedouins, 26 Druze, and 26 others) aged 1 to 21 years, who were diagnosed with ALL between 1989 and 2011 and were treated according to the same Berlin‐Frankfurt‐Muenster–based Israel National Study protocols. Results: Bedouins had a higher incidence of t(1;19) (16% vs 3% for non‐Bedouins) and a lower incidence of high‐hyperdiploidy (10% vs 25% for non‐Bedouins) ( P  = 0.01). Five‐year event‐free survival (EFS) and overall survival (OS) were poorer for the Bedouins (60.3% ± 7.2% and 63.1% ± 7.2%, respectively) compared with the Jews, Muslims, and Druze (80.4% ± 1.4%, 77.3% ± 3.2%, and 84% ± 7.3%, respectively, for EFS [ P  = 0.02], and 86.3% ± 1.2%, 82.3% ± 2.9%, and 88.3% ± 6.4%, respectively, for OS [ P  = 0.002]). Adherence to intensive chemotherapy was similar between the Muslims and the Bedouins. Conclusions: Our findings suggest that the Bedouins, a highly inbred ethnic Arab people, may be considered a higher risk group that may need more intensive chemotherapy and/or supportive care in order to improve their outcome.